La política urbana metropolitana frente a la globalización - Coraggio, José Luis (Revista EURE - Revista de Estudios Urbano Regionales, 1997)
The article argues that, faced to the impact of globalization, Latin American metropolis can and should reorient urban policies towards sustainable human development. It is anticipated that, in the quest to realize genuine local goals, urban policies will enter in confrontation with the dominant macroeconomic policy. In order to ensure coherence between macro and micro levels, the World Bank proposes cities to adjust to a macropolicy that is unilaterally dictated from the needs of global capital. Taking another stand, the author argues in favor of a bottom-up rectification of macropolicies, only way to ensure the contextual requirements to make social and economic agency coherent with a project of sustainable human development. The forces working towards the enhanced reproduction of life should be liberated with the same conviction and political will that market forces were liberated and it is with that perspective in mind that urban conditions for the accumulation of capital should be negotiated. This requires promoting a third pole in the urban economy -popular economy- together with capitalist entrepreneurial economy and public economy. For that purpose, actions and resources currently utilized in an assistencialist manner should be reoriented to enabling the development of new self-sustainable economic structures as well as cultural institutions required for social integration and effective democratization. The necessary corrections to macropolicies would emerge in the process of consolidating such third pole. Given its weight and its capacity to generate new synergies that are essential to overcome the anomia and fragmentation now prevailing, metropolitan cities may greatly contribute to defining a new social project for the next century. Í 